Design of Prototype Metode Waterfall: Optimasi Tata Kelola Kearsipan pada Koperasi Batang Cemerlang Kabupaten Batang - Mulyapradana, Aria; Anjarini, Ary Dwi; Darmawan, Wachid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Rob disasters pose a serious threat to coastal areas and have an impact on activities and damage to physical facilities, one of which is damage to important documents. This impact was also felt by the Batang Cemerlang Cooperative, which is located in the tidal disaster area. Several documents owned by the Batang Cemerlang Cooperative were badly damaged so they could not be saved. Besides, archive management is still done manually and there is a lack of archive storage space, so there is a buildup of files on the work desk, which means there is a need. handling of archive storage, therefore an application is needed to manage archives so that documents can be saved from tidal disasters, easy to access anytime and anywhere and easy to search for documents so that archive management is more effective and efficient. The aim of this research is to facilitate archive storage and save archives from damage due to tidal disasters. Therefore, the archive application is a solution to overcome the problems faced by the Batang Cemerlang Cooperative. The methods used to create archive applications are the research and development (R&D) method and the Design of Prototype Waterfall Method. The result of this research is an archive application, where this application has several features in archive management including a dashboard display, display of incoming and outgoing mail, and display of input document reports along with file attachments. This application is easy to use and can be accessed anywhere so that users can carry out archive management activities and rescue documents from tidal disasters